(untitled) (Global Journal of Management and Business Research, 2017)
The purpose of this study is to empirically investigate the impacts of satisfaction on eservice quality, trust and on e-loyalty in online marketing. The theoretical background used in this study was social exchange theory. Online survey from students and faculty members of Kathmandu University, Nepal was conducted in this study. The analytical results indicate that e-service quality, customer service, and trust have strong direct effect on satisfaction and impacts of indirect effects with e-loyalty are more significant. Findings also indicated that satisfaction was a significant variable that mediated the relationships between service quality and customer loyalty.